EVALUASI STRUKTUR ATAS BOGOR VALLEY APARTEMEN DAN HOTEL - Anderika Pradhita; Fajar Wahyu Putranto; Sukamta Sukamta; Hardi Wibowo (Jurnal Karya Teknik Sipil, 2014)
Bogor Valley Apartment and Hotel was built in November 2012.This high rise building consists of 2 towers of apartment and 1 tower of hotel. The apartment reaches 63,7m high with 22 stories and 2 semi basements and the hotel has 10 stories with no semi basement.This upperstructure evaluation of Bogor Valley Apartment and Hotel is based on Indonesian Seismic Code (SNI 03 – 1726 – 2012). Structure is modeled as similar as possible to existing structure. Structural element represents detail section in As Built Drawing. Loading structure in the form of dead load, live load, and seismic load. This structure has irregular shape and high enough stories so therefore using dynamic seismic load analysis is more suitable. Upper structure analysis is using SAP2000v14. As the result of calculations showed that structural element of Bogor Valley Apartment and Hotel building needs to be reviewed deeper because there are some elements that cant pass the requirements based on analyze of Indonesian Concrete Code (SNI 03 – 2847 – 2002).